2017
DOI: 10.1186/s11671-017-2319-y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanoscale Pits with High Throughput on Polymer Thin Film Using AFM Tip-Based Dynamic Plowing Lithography

Abstract: We show that an atomic force microscope (AFM) tip-based dynamic plowing lithography (DPL) approach can be used to fabricate nanoscale pits with high throughput. The method relies on scratching with a relatively large speed over a sample surface in tapping mode, which is responsible for the separation distance of adjacent pits. Scratching tests are carried out on a poly(methyl methacrylate) (PMMA) thin film using a diamond-like carbon coating tip. Results show that 100 μm/s is the critical value of the scratchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To date, nanodots/pits, nanogrooves/lines, and even three-dimensional (3D) complex structures have been achieved on these films by using the TBN method. Various types of nanomachining methods based on tips involving static scratch [33][34][35], DPL [9,13,14,36,37], and vibration-assisted approach [22,[38][39][40][41][42][43][44][45][46], especially the ultrasonic vibration-assisted (UV-assisted) method, have been used to machine nanopatterns on polymer films (Table 1). Heated tips have been found to offer important advantages in machining polymer film materials.…”
Section: Machining On Polymer Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, nanodots/pits, nanogrooves/lines, and even three-dimensional (3D) complex structures have been achieved on these films by using the TBN method. Various types of nanomachining methods based on tips involving static scratch [33][34][35], DPL [9,13,14,36,37], and vibration-assisted approach [22,[38][39][40][41][42][43][44][45][46], especially the ultrasonic vibration-assisted (UV-assisted) method, have been used to machine nanopatterns on polymer films (Table 1). Heated tips have been found to offer important advantages in machining polymer film materials.…”
Section: Machining On Polymer Thin Filmsmentioning
confidence: 99%
“…On the surface of polymer films, nanodot arrays can be fabricated via tip nanoindentation directly or through the overlap of two machined nanogrooves by a single scratch performed twice in different directions [13,36]; a third scratch may be employed to improve density [13]. Nanopits have been obtained using a tip that is pressed into a sample, similar to nanoindentation [1] or DPL based on tapping [9,37]. Some scholars have found that heated tips can modify polymer surfaces by changing their properties by heating.…”
Section: Machining On Polymer Thin Filmsmentioning
confidence: 99%
“…Many scholars have obtained nanopits using the TBN method and studied the influence of scratching parameters on achieved nanopits. He et al [82] used the DPL method, which is based on the tapping mode of AFM to scratch nanopits on PMMA thin films with high efficiency. In this study, a critical scratching velocity was observed to form nanopit.…”
Section: Nanopatterns Fabricated By the Tip-based Nanomachining/namentioning
confidence: 99%
“…Surface morphology images of nano-pit arrays at a scanning speed of 400 μm/s in the scan size of 5 μm measured by AFM: ( a ) 2D images, ( b ) zoom-in image of figure ( a ) at a dimension of 2 μm, ( c ) 3D image of ( b ), ( d ) cross-section of ( b ) [82]. …”
Section: Figurementioning
confidence: 99%
“…Effective management of the processes and phenomena occurring at these scales makes it possible to purposefully create materials with fundamentally new characteristics unattainable with the use of traditional technologies. Nowadays atomic force microscopy (AFM) is one of the most promising tools for such studies [1][2][3][4][5]. Its main advantage over conventional electron microscopy is that the AFM allows us to obtain information not only about the topology of the internal structure of the material, but also about its local physical properties.…”
mentioning
confidence: 99%